THE EVALUATION OF MOTOR COMPETENCE IN TYPICALLY DEVELOPING CHILDREN: AN INTEGRATIVE REVIEW - Luz, Carlos (2018)
The development of motor competence (MC) is essential in childhood. In this respect, previous studies have found several positive associations of the MC with physical activity, cardiorespiratory fitness, physical fitness, and perceived physical competence, as well as an inverse association with weight status. The lack of MC during this stage might, therefore, compromise the future adoption of active and healthier lifestyles. This review aimed at listing and examining the different instruments that have been used to evaluate MC in typically developing children, pointing the weakness and strengths from the perspective of Physical Education (PE) teachers. A systematic search of six electronic databases was conducted. Research designs included cross-sectional, longitudinal or experimental/quasi-experimental. Forty-two articles were identified according to the inclusion criteria. A preference for quantitative measures (21 studies) was verified comparatively to a more qualitative approach (13 studies), although eight studies used both measures. Additionally, we have found that 34 studies used standardized protocol tests and eight studies used protocols developed by the authors. In general the protocols exhibited some strong points, however several presented weaknesses that can limit their application in PE classes, such as the excessive amount of time required, the large number of tasks, the ceiling or floor effects, and the fact that not all MC components are simultaneously evaluated. Different instruments and methodologies have been used to evaluate MC. Finally, a quantitative standardized protocol test is suggested, with proper reliability and validity, which can be used by physical education professionals